Widowhood and asset inheritance in sub-Saharan Africa: Empirical evidence from 15 countries - Peterman, Amber (Wiley, 2012)
Widows in sub‐Saharan Africa (SSA) are perceived to face discrimination in asset inheritance, leading to poverty for themselves and their children. However, large‐sample empirical research supporting this claim is scarce. This article explores asset inheritance among widows using two data sources: (i) nationally representative demographic and health survey (DHS) data from 15 SSA countries, and (ii) a 13‐year longitudinal panel from the Kagera region in north‐west Tanzania. Results indicate that, across the 15 DHS countries, less than half of widows report inheriting any assets; the proportion reporting inheriting the majority of assets is lower. Findings from Kagera indicate that the value of inheritance is significant in determining changes in long‐term household welfare.